Non-market approaches within the Paris Agreement: Implementation progress, examples and COP29 expectations - Villarino, Ma. Eliza J. (CGIAR Impact Platform on Climate Change, 2024)
Article 6.8 of the Paris Agreement establishes non-market approaches (NMAs). These enable countries to voluntary cooperate in climate action through mitigation, adaptation, and sustainable development, without relying on carbon markets. CGIAR’s climate innovations have the potential to contribute to NMAs, with 35 out of 62 innovations integrating both mitigation and adaptation. These innovations could demonstrate how NMAs can address climate resilience, food security and environmental sustainability. A rapid assessment tool is needed to identify and scale NMAs, ensuring they align with the goals of the Paris Agreement. This would help streamline the identification process and facilitate implementation of NMAs to support mitigation, adaptation, and sustainable development.